Study of Pharmaceutical Provision Under the Program of Medical Guarantees in Ukraine - Pyndus, Volodymyr; Shapovalov, Valentyn (SSP Modern Pharmacy and Medicine, 2024)
Ukraine has implemented a comprehensive Medical Guarantees Program, which encompasses both medical and pharmaceutical services. One of the key components within the pharmaceutical services is the provision of pharmaceutical supplies. For the first time, an in-depth study was conducted into patient referrals for both medical services and pharmaceutical support under this program. The research involved an analysis of patient appeals, considering seven key indicators: financial resources, electronic medical records, patient declarations, the provision of medical services, the timeliness of pharmaceutical delivery, adherence to ethical standards in patient treatment, and other aspects of medical and pharmaceutical service delivery. Furthermore, a clinical and pharmacological analysis of drug-related complaints was performed using the ATC classification system, with 19 specific ATC codes being examined. This research highlights the crucial role that patient feedback plays in enhancing Ukraine’s healthcare system, ultimately leading to improved quality in the provision of medical and pharmaceutical services. The analysis of patient appeals and the identification of specific areas for improvement demonstrate a commitment to addressing the needs of the population. Moreover, by incorporating the ATC classification system into the analysis, the research provides a structured approach to understanding and resolving pharmaceutical issues, which is vital for maintaining the safety and efficacy of treatments provided to patients. This ongoing research is expected to contribute valuable insights that will support the continuous development of Ukraine's healthcare system, aligning it with international standards and best practices.